Perbedaan Determinan Stunting Balita pada Dua Kabupaten dan Kota dengan Prevalensi Tinggi dan Rendah: Differences in Stunting Determinants among Under-Five Children in a High and Low Prevalence Region in Indonesia - Briawan, Dodik; Widodo, Yekti; Srirezeki, Yulia (Jurnal Ilmu Gizi dan Dietetik, 2025)
Indonesia was ranked 59th in the human capital index (HCI) among 117 countries with the low middle income. Stunting child free percentage is one of the HCI’s measurement indicator. The results of the 2022 Indonesian Nutritional Status Survey (SSGI) 2022 showed Banten Province was a high prevalence of stunting (20%).  Banten determined as a priority province for accelerating stunting reduction in Indonesia. Selected research region were Pandeglang District as a high stunting prevalence (29,4%) and South Tangerang City as a low stunting prevalence (9%) based on the 2022 SSGI. This study aimed to analyze differences stunting determinants between South Tangerang City and Pandeglang District. This type of research utilized secondary data from the 2022 SSGI results. SSGI 2022 used a cross-sectional study design. The Subject were under five (0-59 months) with a total of 551 in South Tangerang city and 291 Pandeglang district with total number 842 under five. Data were analyzed using SPSS 22 application. Binary Logistic Regression with 5% significancy and 95% confident interval was used for the data analyzation. Stunting determinants in Pandeglang district were lived in rural (OR= 2,251), low birth length (OR= 2,559), and diarrhea (OR= 3,157). Poor sanitation (OR= 31,328) was stunting determinant in South Tangerang city. Stunting reduction interventions in Pandeglang District are needed comprehensively at both individual and household levels, while in South Tangerang City at the household level.